Microbiota-dependent presence of murine enteric glial cells requires myeloid differentiation primary response protein 88 signaling - Enderes, Jana; Neuhaus, Hannah; Basic, Marijana; Schneiker, Bianca; Lysson, Mariola; Kalff, Jörg C; Wehner, Sven (Journal of biosciences, 2023)
Enteric glial cells (EGCs) were shown to maintain the barrier integrity and immune homeostasis of the bowel. Postnatally, EGCs develop from progenitor cells located in the myenteric plexus and are continuously replenished through adulthood. Both, murine EGC development and replenishment were shown to depend on the microbiome. The underlying mechanisms are still unknown, and we hypothesized that the myeloid differentiation primary response protein 88 (Myd88) or toll-like receptor signaling pathways may be involved. Adult and neonatal C57BL/6 wild-type (wt) and Myd88 −/− mice were housed under specific pathogen-free (SPF) or germ-free (GF) conditions. GF mice were further conventionalized by gavaging stools from, and cohousing with, SPF mice having intact microbiomes. The small bowels were harvested at various time points, and immunohistochemistry and qPCR analysis of EGC markers in the muscularis externa and mucosa were performed. In wt mice, after conventionalization, the glial cell-specific markers, glial fibrillary acidic protein (GFAP) and S100 calcium-binding protein β (S100β), were upregulated in the mucosa and muscularis externa. In Myd88 −/− mice, this upregulation did not occur. Importantly, GFAP (only in the mucosa) and S100β (in both the mucosa and muscularis externa) were significantly reduced in conventionalized Myd88 −/− mice compared with the conventionalized wt mice. In neonatal mice, the gene expressions of GFAP and S100β increased between the day of birth (P0) and postnatal day 15 (P15) in the mucosa and muscularis externa of both wt and Myd88 −/− mice. Notably, in the mucosa but not the muscularis externa, at P15, the gene expressions of GFAP and S100β were significantly reduced in Myd88 −/− . Our data demonstrated that postnatal development and replenishment of EGCs require intestinal microbiota and depend on Myd88. The specific upstream mechanisms may involve toll-like-receptor recognition of the microbiota and will be the subject of further research.